Law enforcement training and the domestic far right - Chermak, Steven M. (Criminal justice and behavior, 2009)
This article examines issues related to training as it pertains to domestic terrorism in general and responding to far-right extremists in particular. First, it hightlights current training practices and training focused on the far right. Second, it details knowledge about the nature and extent of the threat posed by far-right extremists. Third, a review of the empirical research indicates that training could be enhanced if three key issues are emphasized: Future training should promote a better understanding of the contours of the far right; discuss the unique geographic, crime-incident, and structural characteristics of the far right; and describe the need to examine all ideologically motivated crimes, regardless of whether they are also defined as terrorist. The conclusion discusses how training could be enhanced by strategically integrating the existing knowledge base.